Carrier pwm technique to reduce switching for 5 levels h brigde npc inverter - Quach, Thanh Hải; Do, Đức Trí; Bui, Minh Ẩn (Journal of Technical Education Science, 2016)
A new carrier pulse width modulation with a novel offset base to reduce switching times and thus, all switching loss in five-level H-brigde neutral point clamped inverter will be presented in this paper. The proposed technique uses the offset which is the 3rd voltages to transfer the control voltage into the extremum levels of each carrier in a discontinuos manner. This transferring depends on the distances of control voltage to levels is minimum. So that in this research five levels of carrier will be used to reduce the intersection of control and the carrier wave to reduce the amount of switching losses. With the pulse width modulation method and flexible offset voltages in this study, the number of switchings/phase in a cycle can be reduced by about 33% in theory and 15.25% in experimental at f carrier frequency 3000Hz. Simulation and experimental results are provided in order to validate the proposed method